2020
DOI: 10.1016/j.jnc.2020.125822
|View full text |Cite
|
Sign up to set email alerts
|

One rule does not fit it all: Patterns and drivers of stakeholders perspectives of the endangered Iberian wolf

Abstract: Public attitudes are vital for the successful implementation of management strategies and conservation programs. However, contradictory interests among different stakeholders can create important setbacks, creating barriers to achieve conservation goals. The endangered Iberian wolf (Canis lupus signatus) occupies now only 20% of its historical distribution area, in Portugal, and its reduction was mostly due to direct human persecution. Here, we assessed locals' attitudes towards the Iberian wolf in northeast P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…Our findings align with previous research showing residents near endangered species restoration sites have more negative attitudes and decreased support for conservation action (Eriksson, Sandström, & Ericsson, 2015;Karlsson & Sjöström, 2007). Negative attitudes toward endangered species reintroductions are often related to the potential, or perceived potential, for the target species to threaten human safety, damage property, or limit land management practices (Miller et al, 2016;Torres et al, 2020). In the case of ferret recovery, our findings support previous studies that suggested persistent negative attitudes seem to be related to federal policy and to impacts of measures taken to conserve prairie dogs Reading & Kellert, 1993).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings align with previous research showing residents near endangered species restoration sites have more negative attitudes and decreased support for conservation action (Eriksson, Sandström, & Ericsson, 2015;Karlsson & Sjöström, 2007). Negative attitudes toward endangered species reintroductions are often related to the potential, or perceived potential, for the target species to threaten human safety, damage property, or limit land management practices (Miller et al, 2016;Torres et al, 2020). In the case of ferret recovery, our findings support previous studies that suggested persistent negative attitudes seem to be related to federal policy and to impacts of measures taken to conserve prairie dogs Reading & Kellert, 1993).…”
Section: Discussionsupporting
confidence: 88%
“…Increasingly, human dimensions are acknowledged as a leading factor influencing the success of endangered species recovery (Esmaeili, Hemami, & Goheen, 2019;Hadlock & Beckwith, 2002). This is particularly the case for carnivore species that are often viewed as direct threats to human safety, damage property, or limit land use practices (Miller, Jhala, & Schmitz, 2016;Torres, Lopes, Fonseca, & Rosalino, 2020). For example, even where adequate habitat for tigers (Panthera tigris) exists in India, recovery of this species has been challenged by persistent human-tiger conflict, leading to further animosity toward its recovery (Goodrich, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, sex, age, and education may play a key role in fostering positive attitudes. In general women, elderly people, people with a lower level of education and less knowledge of the target species show less tolerance [34][35][36]. Secondly, folklore referring to oral traditions, folk tales, culturally transmitted fear, distaste or love towards certain groups of animals may lead to important conservation issues as some species may survive to the detriment of others [37][38][39].…”
Section: Theoretical Framework: the Perceptions Towards Bears And Wolvesmentioning
confidence: 99%
“…Secondly, folklore referring to oral traditions, folk tales, culturally transmitted fear, distaste or love towards certain groups of animals may lead to important conservation issues as some species may survive to the detriment of others [37][38][39]. Thirdly, people living in rural areas are generally less tolerant than urban inhabitants [35,36,[40][41][42], which in turn is linked to another factor that may drive people's attitudes, i.e., direct experience with carnivores [34,36]. Urban interests are perceived as the dominating norm in society driving political processes and controlling policymaking processes [43].…”
Section: Theoretical Framework: the Perceptions Towards Bears And Wolvesmentioning
confidence: 99%
“…Hunters and hunting traditions have also come to the fore regarding conservation of large carnivores (Ericsson & Heberlein, 2003;Treves, 2009). Hunters often report negative attitudes towards carnivores, and in particular towards wolf establishment, in addition to representing a strong voice in social debates about wildlife management (Agarwala et al, 2010;Karlsson & Sjostrom, 2007;Naughton-Treves et al, 2003;Torres et al, 2020). Researchers, on the other hand, often pinpoint how the politically set management goals for wolves are too low to achieve an ecologically sustainable population, that hunting of wolves should be restricted and these low population sizes will lead to negative factors like inbreeding depression (Akesson et al, 2016;Nilsson, 2004).…”
Section: Introductionmentioning
confidence: 99%